A study on stability of earthen site restoration by solidified soil containing calcined ginger nuts - Dandan Li; Erxing Peng; Yaling Chou; Xiaoying Hu (Case Studies in Construction Materials, 2023)
Erosion is a disease of elevation concavity formed on earthen sites by the action of water, salt, wind, rain, and other activities alone or in combination. Due to the different positions of the elevation concavity, it is divided into bottom and middle erosion. Considering the Niutoucheng site as the background, its stability was analyzed with different erosion forms before and after restoration using the solidified soil of calcined ginger nuts (CGN) with the optimum dosage in earthen sites by performing finite element analysis. Middle and bottom erosion models were established based on the original appearance of the earthen site where the most significant erosion existed, and the parameters of the restoration area were obtained by direct shear testing. Further, the safety factor was investigated under different erosion forms and curing ages. The safety factor is the strength reduction factor when critical failure is reached. Before restoration, the safety factors of the middle and bottom erosion models were 0.9479 and 1.3245. After 7, 14, 28, and 60 days of restoration, the safety factors of the middle erosion model are 1.5484, 1.5523, 1.5536, and 1.5543, respectively, the safety factors increased by 63.35%, 63.76%, 63.89%, and 63.97%, respectively; the safety factors of the bottom erosion model are 1.5756, 1.5859, 1.5913, and 1.5993, and the safety factors increased by 18.96%, 19.74%, 20.14%, and 20.75%, respectively. The earthen sites restored by calcined ginger nuts solidified soil are in a stable state. The results of this study provide a theoretical basis for evaluating the effect of the CGN to restore the erosion area and references for similar restoration projects of earthen sites in the future. In particular, it provides guidance for construction dosage.